2005
DOI: 10.1111/j.1423-0410.2005.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a malarial antibody enzyme immunoassay for establishing the reinstatement status of blood donors potentially exposed to malaria

Abstract: The study findings support the efficacy and safety of a targeted screening strategy combining antibody screening with a 6-month cellular component restriction period for donors with a declared malarial risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 25 publications
3
42
0
5
Order By: Relevance
“…Among commercial antibody tests where the source and/or composition of solid-phase antigens is known (e.g., Lab 21 Healthcare [42], DiaMed [16], and several Korean assays [see reference 30]), the absence of P. ovale-or P. malariae-derived antigens suggests that detection of antibodies to these species must rely on antibody cross-reactivity to P. falciparum or P. vivax antigens-unless reactivity is due to the persistence of P. vivax or P. falciparum antibodies from previous infections. We detected P. vivax MSP1-p19 IgG reactivity among all individuals with microscopy-confirmed P. ovale infection for whom IFA exhibited the presence of both P. ovale and P. vivax antibodies (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among commercial antibody tests where the source and/or composition of solid-phase antigens is known (e.g., Lab 21 Healthcare [42], DiaMed [16], and several Korean assays [see reference 30]), the absence of P. ovale-or P. malariae-derived antigens suggests that detection of antibodies to these species must rely on antibody cross-reactivity to P. falciparum or P. vivax antigens-unless reactivity is due to the persistence of P. vivax or P. falciparum antibodies from previous infections. We detected P. vivax MSP1-p19 IgG reactivity among all individuals with microscopy-confirmed P. ovale infection for whom IFA exhibited the presence of both P. ovale and P. vivax antibodies (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available ELISAs have been developed that use recombinant antigens or P. falciparum whole-organism lysates for detection of immunoglobulins (IgG and/or IgM, IgA) in human serum or plasma (Lab 21 Healthcare Laboratories, United Kingdom; Cellabs, Australia; DiaMed AG, Switzerland; LG Chemical Inc., Iksan, South Korea; Green Cross, Inc., Youngin, South Korea [Genedia Malaria Ab Rapid]; and Standard Diagnostics, Suwon, South Korea). These assays are typically easier to perform and exhibit higher throughput and better sensitivity and specificity than IFA (25,42,47), though this is not always the case (32). Some ELISAs may be better than others for detection of antibodies against all four Plasmodium species that cause malaria in humans (44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This manual method depends on maintaining consistency of examination of thin smears of P. falciparum asexual blood stages by trained microscopists making inter-laboratory standardization challenging (Seed et al, 2005b;Elghouzzi et al, 2008). Alternative enzyme immune assays (EIA) and ELISAs have been developed and some studies (Kitchen et al, 2004;Seed et al, 2005a;Doderer et al, 2007;Elghouzzi et al, 2008) found comparable diagnostic sensitivity between IFAT and EIA/ELISA whereas others (Silvie et al, 2002) did not. Most EIA/ELISAs utilize one to four antigens for detection of malaria specific antibodies.…”
Section: Introductionmentioning
confidence: 97%
“…Because malaria is increasingly viewed as a blood availability issue, alternative solutions to this quandary are frequently proposed. [11][12][13] Accurate data reflecting the impact of these deferrals are required to develop rational approaches to increase blood availability, while ensuring or enhancing blood safety. Herein, we report on the trends associated with malaria deferrals in American Red Cross (ARC) system over a 7-year period and their impact on blood availability.…”
mentioning
confidence: 99%